585 Natural history of left ventricular hypertrophy in infants of diabetic mothers. (8th December 2021) - Monda, Emanuele; Verrillo, Federica; Lioncino, Michele; Altobelli, Ippolita; Caiazza, Martina; Rubino, Marta; Cirillo, Annapaola; Fusco, Adelaide; Mauriello, Alfredo; Amodio, Federica; Di Fraia, Francesco; Pacileo, Roberta; et al.
Abstract: Aims: This study sought to describe the characteristics and the natural course of left ventricular hypertrophy (LVH) in a well-characterized consecutive cohort of infants of diabetic mothers (IDMs). Methods and results: Sixty consecutive IDMs with LVH have been retrospectively identified and enrolled in the study. All IDMs were evaluated at baseline and every 6 months until LV wall thickness regression, defined as the decrease of wall thickness measurement into the normal reference range for cardiac parameters ( z -score > −2 and <2). A comprehensive assessment was performed in those patients with diagnostic markers suggestive of a different cause and/or without significant reduction of the LVH during follow-up. At 1-year follow-up, all IDMs showed a significant reduction of maximal wall thickness MWT [6.00 mm (IQR: 5.00–712) vs. 5.50 mm (IQR: 5.00–6.00), P -value <0.001; MWT- z -score: 4.86 (IQR: 3.93–7.61) vs. 1.72 (IQR: 1.08–2.85), P -value <0.001] compared to baseline, and all patients showed LV wall thickness regression or residual mild or moderate LVH (57%, 28%, and 12%, respectively), except two patients with persistent severe LVH, that after a comprehensive clinical-genetic assessment were diagnosed as Noonan syndrome with multiple lentigines. At multivariate analysis, MWT was negatively associated with LV wall thickness regression at 1-year follow-up [MWT-mm: OR: 0.48 (0.29–0.79), P -value = 0.004; MWT- z -score: OR: 0.71 (0.56–0.90), P -value = 0.004]. Conclusions: LVH in IDMs represents a benign condition with complete regression during the first years of life. In those patients without LV wall thickness regression, combined with clinical markers suggesting a specific disease, a complete work-up is required for a definite diagnosis.